The adoption of electronic banking in Namibia: The case of small and medium enterprises - Nuuyoma, Thomas (Graduate School of Business (GSB), 2020)
Electronic (internet and mobile) banking is inevitably the future way of banking across all market spectrum in Namibia. Although most business categories have migrated to the technological banking, small and medium enterprises (SME) business operator are still utilising the conventional and traditional method of banking particularly those in the least developed area of the country. The objective of this research is to study and assess the factors that influence the behavioural intention to use and actual usage of electronic (mobile and internet) banking services among SMEs in Namibia. This study utilizes quantitative approach by administering survey questionnaires to collect data from the targeted sample of 132 SMEs in three towns of Otjiwarongo, Oshakati and Outapi. The study has used structured questionnaires based on the UTAUT2 model to assess and provide answers to the factors that affect the behavioral intention to use and usage behaviour of mobile and internet banking. The data were analysed using confirmatory factor analysis to examine the reliability, composite reliability and average variances explained of the constructs assessed. Finally, ordinary least squares and logistic regression techniques were employed to identify the explanatory of behavioural intention to use and usage behaviour of electronic banking services. From the analysis, the results shows that factors such as performance and effort expectancy, social influence and facilitating conditions influence the acceptance of the banking technologies however habit has been found to have a considerable prediction power in explaining the behavioural intention to use internet and mobile banking among SMEs in Namibia to adopt the electronic banking while facilitating condition and habit are the strongest drivers of the acceptance of technology in the consumer settings. The study provides practical recommendations and challenges to banks, regulator and mobile operator to develop alternative strategies to absorb the SME sector into the new banking platform.